Adaptation of the didactic methodology to virtuality in the technical processing courses of the School of Library and Information Sciences of the University of Costa Rica - Calvo, Desiree Rodríguez (2021)
This article identify the student perception of the adaptation of the didactic methodology to virtuality in the technical processing courses BI-2001 Cataloging I and BI-3001 Indexing, at the School of Library and Information Sciences of the University of Costa Rica, during the I school year of 2020. To achieve this objective a quantitative research was carried out in which an online questionnaire was applied to analyze aspects such as the access they have to virtual classes, perception regarding the applied didactic methodologies. It is observed that having an adequate internet access is essential to continue with the educational process under the virtual modality, as well as the importance of adapting the didactic materials and assessments that were traditionally carried out in person, considering the factors that intervene in the virtual education.